Prevalence and Predictors of Diabetic Peripheral Neuropathy in Newly Diagnosed Type 2 Diabetes Mellitus Patients - Jadhao, Pooja; Swain, Jayshree; Das, Srijit; Mangaraj, Swayamsidha; Sravya, Surapaneni Lakshmi (Current Diabetes Reviews, 2025)
AimThe present study aimed to determine the prevalence and predictors of DPN in newly diagnosed T2DM patients.BackgroundDiabetic Peripheral Neuropathy (DPN) is the most common and debilitating complication of Type 2 Diabetes Mellitus (T2DM).MethodsNewly diagnosed T2DM patients visiting the outpatient department were recruited. Detailed demographic parameters, histories, physical examinations, and biochemical investigations were carried out. Patients were screened for DPN using the Diabetic Neuropathy Symptom (DNS) score, the revised Disability Neuropathy Score (NDS), Vibration Perception Threshold (VPT) using a biosthesiometer, and the 10 g SW Monofilament Test (MFT).ResultsA total of 350 newly diagnosed T2DM patients (mean age 46.4±13.6 years) were included. The prevalence of DPN was found to be 34% using the combined DNS and NDS scores. VPT was moderately impaired in 18.3% and severely impaired in 12% patients, while MFT revealed a loss of protective sensation in 35.4% patients. After logistic regression analysis, DPN was significantly associated with increasing age (OR 1.08, 95%CI 1.06-1.11), increasing HbA1C levels (OR 1.23, 95%CI 1.05-1.42), increasing TSH levels (OR 1.23, 95%CI 1.05-1.44), presence of hypertension (OR 2.78, 95%CI 1.51-5.11), and reduced BMI (OR 0.9, 95%CI 0.84-0.99). The sensitivity and specificity of detecting DPN by combining VPT and MFT were 91.6% and 84.2%, respectively.ConclusionThe prevalence of DPN was high even in newly diagnosed T2DM and associated significantly with increasing age, HbA1C levels, TSH levels, hypertension, and reduced BMI. Earlier screening for DPN, along with aggressive control of glycemia, blood pressure, and hypothyroidism, may be beneficial.
Keywords: diagnosis